2022
DOI: 10.1186/s13046-022-02564-2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G2 in macrophages triggers CTL-mediated antitumor immunity and antiangiogenesis via interferon-gamma

Abstract: Background IFN-γ is a key mediator of tumor immunity that can induce macrophage polarization to suppress tumor growth. Cyclin G2 functions as a tumor suppressor in various cancer cells; however, its role in macrophages remains unclear. This study aimed to investigate the role and underlying mechanisms of cyclin G2 in macrophages in vitro and in vivo. Methods Mouse tumor models were used to determine the effect of cyclin G2 in macrophages on tumor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…Western blot analysis in Figure c and Figure S11 revealed that the pro-apoptotic protein expression of Bax increased and the anti-apoptotic protein expression of Bcl-2 and Survivin decreased in the PAG+NIR group, leading to a decrease in the Bcl-2/Bax ratio. Meanwhile, MAPK/ERK and PI3K/Akt pathways were detected because they are the main downstream pathways of the VEGFR signaling pathway . As expected, the results indicated that the phosphorylation of ERK and Akt was downregulated after treatment with PAG+NIR.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…Western blot analysis in Figure c and Figure S11 revealed that the pro-apoptotic protein expression of Bax increased and the anti-apoptotic protein expression of Bcl-2 and Survivin decreased in the PAG+NIR group, leading to a decrease in the Bcl-2/Bax ratio. Meanwhile, MAPK/ERK and PI3K/Akt pathways were detected because they are the main downstream pathways of the VEGFR signaling pathway . As expected, the results indicated that the phosphorylation of ERK and Akt was downregulated after treatment with PAG+NIR.…”
Section: Resultssupporting
confidence: 64%
“…Meanwhile, MAPK/ERK and PI3K/Akt pathways were detected because they are the main downstream pathways of the VEGFR signaling pathway. 42 As expected, the results indicated that the phosphorylation of ERK and Akt was downregulated after treatment with PAG+NIR. To further verify the mechanism of drug action, immunofluorescence staining of p-Akt and p-ERK was performed.…”
Section: Photothermal Effect and Drug Releasesupporting
confidence: 75%
See 2 more Smart Citations
“…23 G2 checkpoints, which prevent cells from undergoing mitosis when DNA damage is uncontrollable, may be a repair opportunity for self-healing. 39 Flow cytometry showed that PS-MPs increased the G2/M phase of CIK cells and decreased the G0/G1 phase proportion.…”
Section: Discussionmentioning
confidence: 98%